Education Obtained and Occupation Held in Four Industrial Nations - Arnold, John Robert (My University, 1987)
This dissertation examines the strength of association between education and occupation, and the relative occupational advantages of particular types of education, in four nations. Comparisons of the strength of association were intended as a partial test of a hypothesis put forward by Featherman, et al. (1975), that mobility processes in Western societies are essetially alike. Comparisons of the relative standing of particular forms of education were designed to test a series of hypotheses derived from Turner's classic distinction between sponsored and contest mobility. Pairwise comparisons between Canada and the other three nations showed that, on the strength of association between education and occupation, only English males differed significantly from Canadians: for the English education and occupation were less strongly linked. Hypotheses derived from Turner were largely confirmed. University degrees were of higher relative standing in England than in Canada and in Canada than in the United States. A selective secondary school program offered greater advantage over a non-selective program in either England or West Germany than an academic high school program offered over a vocational program in Canada. A literature search has revealed no previous multi-nation comparisons of the strength of association in occupation by education tables, and no multi-nation test of the hypotheses derived from Turner. The tests have been made through Goodman's multiplicative Row-Column model, which has not been applied to occupation by education tables in the previously published literature. Standard errors and goodness-of-fit tests were obtained from the stratified multi-stage samples employed through jackknifing, which provides more useful results than those obtained by authors who have treated the stratified multi-stage samples employed in national mobility studies as if they were simple random samples.
Keywords: Sociology; Sociology